Correction of movement patterns of skaters through feedback on the distribution of plant pressure in speed running - Sushchenko, V. P.; Vasyuk, V. E.; Bykov, D. Y. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the possibilities of correcting movement patterns of speed skaters using feedback on the distribution of plantar pressure in speed running.